Modeling of a quarter bridge frequency converter of the inductive heating systems - Sabokar, O.; Сабокарь, О. С.; Сабокар, О. С. (Харківський національний автомобільно-дорожній університет, 2014)
In this article a review of existing realizations of the induction heating system frequecy converter and its working principles was done. Described the need for a simpler and more reliable frequency converter voltage supply scheme. The paper presents the concepts scheme, analytical dependences according to the circuit calculations and corresponding graphs of current interest dependencies. Proposed conclusions and recommendations for the implementation of the described scheme.
Моделирование четверть мостового преобразователя частоты для установок индукционного нагрева
Моделювання чверть мостового перетворювачів частоти для установок індукційного нагріву
Keywords: Induction heating; control system; the resonance frequency; switching currents; индукционный нагрев; система управления; резонансная частота; токи коммутации; індукційний нагрів; система управління; резонансна частота; струми комутації; 621.3.014.4